Policies to Control and Evaluate Regional Regulations on Taxes and Levies in Indonesia: Re-centralisation? - Ambarwati, Sinta Devi; Sudarsono, Sudarsono; Hadiyantina, Shinta (Jurnal Media Hukum, 2023)
The research analyses whether the regulations concerning the mechanisms of control and evaluation of regional regulations on taxes and levies, as outlined in Law No.1 of 2022, comply with the concept of regional autonomy in Indonesia. With normative juridical approach, this research found that the mechanisms of control and evaluation of regional regulations on taxes and levies do not comply with the concept of regional autonomy. However, such mechanisms are required in Indonesia as a unitary state that is based on autonomy, since no system of autonomy works in the absence of control. Nonetheless, in this case, the supervisory authority given to the central government, in the form of preventive and repressive supervision, tends to cause too much interference in the process of shaping policies regarding regional taxes and levies, which should be within the authority of regional governments. Therefore, assertive and specific provisions should be made to prevent intervention by the central government that goes beyond what is required